Main Indications and Outcomes of Hysterectomy among Iraqi Women in Al-Najaf –A Clinical Evaluation Study - Masar Raheem Abbas; Nadia Abdulmunem Sahib Alhamami; Nisreen Hussein Abdulsada (Academic Journal of Clinicians, 2022)
At present, hysterectomy continues to be the most performed gynecological surgery. Indications and outcomes of this procedure still further assessment to identify the appropriateness of these indications. Therefore we aimed to assess the main indications and pathologies behind performing hysterectomy. Hence 100 women who were underwent hysterectomies at Alforat Alawsat teaching Hospital during the period 2018-2020 in Najaf-Iraq were included and their findings were analyzed. Results revealed that Frequency of hysterectomy appeared to be significantly increased with advancing age. Higher number of pregnancies and parities was associated with high rate of hysterectomy uterine fibroid was the more frequent indication contributed for 41%, Elective and total abdominal hysterectomy were the more frequently performed type, 81% and 79%, respectively. Complications included 13% and infection and 9% urinary bladder injury. 15 cases needed admission to ICU and no mortalities reported among cases. In conclusion, the distribution of indications and outcomes of hysterectomy almost follows a pattern similar to that described by national and international studies.